Control of cystic artery during laparoscopic cholecystectomy: clips versus ultrasonic energy devices which is better? - Venkatapuram, Mahidhar Reddy; Sateesh, Sreeram (International Surgery Journal, 2017)
Background: This study was undertaken to know whether clip usage or ultrasonic energy application, obtains better haemostasis of cystic artery during laparoscopic cholecystectomy. Methods: About 80 patients undergoing laparoscopic cholecystectomy were selected on a prospective basis and divided into two equal groups- A and B. a comparative study was done between the two group. Clips were used to control cystic artery in group A patients and ultrasonic energy device was used for the same in group B. Results: In group A, 2 patients had clip slippage intraoperatively which was dealt by reapplication of clips.in group B,1 patient had intraoperative bleeding from cystic artery few minutes after application of ultrasonic energy which was dealt by bipolar cauterization. In both the groups no, postoperative bleeding was encountered. Conclusions: During laparoscopic cholecystectomy, clip usage and ultrasonic energy application are equally competent in achieving haemostasis of cystic artery.